Autoestima e autoeficácia de atletas de futsal feminino - SILVA, Rílary Neves da (2022)
This paper deals with the investigation of psychological constructions in female futsal athletes from Belém / PA. Fifty athletes who practice futsal for at least 1 year, with ages ranging from 15 to 27 years old, average age of 21.4 years old and practice time from 01 to 20 years old (average 7.9 years old) were evaluated. Used or self-esteem inventory for athletes (OKAZAKI, 2004) to evaluate self-esteem and self-efficacy scale of specific tasks in soccer (BRAY; BALAGUER; DUDA, 2004) to assess self-efficacy. Statistical analysis was performed using the Statistical Package for Social Sciences (SPSS) software with a significance level of p ≤0.05. One sample sample had a general average self-esteem of 64.24%, with 36% of athletes at low level, 28% at normal level and 36% at high level. In self-efficacy, the overall average was 66.96%, and 5% of athletes with low-moderate and 95% medium-high scores. In addition, a weak and significant Sperman correlation (rho = 0.650; p = 0.005) was found between self-esteem and self-efficacy. Therefore, this paper demonstrates that even though self-esteem and self-efficacy are related, a high level of self-esteem, it does not necessarily also determine a high level of self-efficacy.